2015
DOI: 10.15446/ing.investig.v35n3.49623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moist air in copper heat sinks: Analysis through the entropy generation minimization criterion

Abstract: Many factors affect heat transfer during the cooling of modern electronic devices. Today, knowledge accrues from modeling, simulation, and experimentation. This allows predicting and calculating features of heat transfer phenomena, to some extent. Examples include the amount of heat generated and removed, the required physical properties of the working fluid, and the required material properties of the heat sink, among other parameters. This article describes some simulation results of using air with a given r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Entropy generation rate in single-phase multi-component flows such as airflow through microchannels was studied in different investigations [79][80][81][82]. In a theoretical investigation [79], studies were reported on entropy generation rate in hydrodynamically and thermally fully developed airflow through parallel plate microchannels with asymmetric heat fluxes on top and bottom walls.…”
Section: Entropy Generation Rate In Single-phase Multi-component Flowsmentioning
confidence: 99%
See 3 more Smart Citations
“…Entropy generation rate in single-phase multi-component flows such as airflow through microchannels was studied in different investigations [79][80][81][82]. In a theoretical investigation [79], studies were reported on entropy generation rate in hydrodynamically and thermally fully developed airflow through parallel plate microchannels with asymmetric heat fluxes on top and bottom walls.…”
Section: Entropy Generation Rate In Single-phase Multi-component Flowsmentioning
confidence: 99%
“…Investigations on Entropy Generation Minimization of moist air flow through bundles of microchannels were reported in Ref. [82]. Moisture transfer irreversibilities were included in entropy generation rate by heat transfer.…”
Section: Entropy Generation Rate In Single-phase Multi-component Flowsmentioning
confidence: 99%
See 2 more Smart Citations